Strife or rhythm? - Eikelboom, Lexi (Primerjalna književnost, 2015)
The capacity of art to contribute to peace is dependent upon beliefs about its political contribution. This article demonstrates how two different theories about the ontological and political significance of art have different political effects.
Keywords: Heidegger, Martin, 1724-1804; Agamben, Giorgio, 1942-; filozofija umetnosti; aesthetics; estetika; književnost in politika